1992
DOI: 10.1159/000186990
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vascular Permeability Factor Production by Ciclosporin in Minimal Change Nephrotic Syndrome

Abstract: In order to ascertain whether ciclosporin (Cs) has an inhibitory effect on the vascular permeability factor (VPF) production, various quantities of Cs were added to T lymphocyte cultures from 8 children with minimal change nephrotic syndrome (MCNS) and the VPF activity of culture supernatants was assayed. As a result of the addition of Cs, a dose-dependent inhibition of VPF production was seen. VPF production was inhibited by a level of between 100 and 250 ng/ml of Cs in vitro. The reduction of proteinuria by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…It has been shown to decrease proteinuria even in patients who are cyclosporine-resistant even though both these agents are calcineurin inhibitors [24, 44, 45]. Possible explanations include better inhibition of vascular permeability factor in patients with minimal change disease compared to cyclosporine [46, 47] and better cytokine suppression [20]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to decrease proteinuria even in patients who are cyclosporine-resistant even though both these agents are calcineurin inhibitors [24, 44, 45]. Possible explanations include better inhibition of vascular permeability factor in patients with minimal change disease compared to cyclosporine [46, 47] and better cytokine suppression [20]. …”
Section: Discussionmentioning
confidence: 99%
“…There are some data to suggest that tacrolimus has differing effects on proteinuria in NS compared with cyclosporine [34,35]. Maruyama et al [36,37] also demonstrated better inhibition of the vascular permeability factor cultured from patients with MCD with tacrolimus than with cyclosporine. Tacrolimus also has better cytokine suppression than cyclosporine, which may also influence the differing responses to therapy [24].…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that corticosteroids can reduce edemaand prevent angiogenesis in patients with a high serum VEGFlevel. Maruyama et al reported that VEGFprotein production is suppressed by cyclosporin A in vitro (19). Cyclosporin A inhibits the activity of calcineurin in the cell through tyrosine kinase-related signal transduction.…”
Section: Discussionmentioning
confidence: 99%